Detection of natural radioactive materials in the soil of bauxite mining areas of Kuantan, Pahang, Malaysia - Sayed, Inayatullah Shah; Mustafa, Madihah (Research Publish Journals, 2016)
Natural radionuclides, such as, Uranium (U-238), Thorium (Th-236), Radium (Ra-226) and Potassium (K-40) are present in the soil. In this study the detection of natural radioactive materials in the soil of bauxite mining areas in Kuantan was determined. Soil samples were collected from three different places. Advanced Nuclear Spectroscopy System with UCS 30 Universal Computer Spectrometer Software and High Sensitivity Gamma Spectroscopy Model SE-9764 with WinDas Software were used. Background radiation energy spectra and soil samples were obtained and compared. The spectra obtained by measuring all samples show the similar pattern as recorded from the background radiation measurement. Therefore, this study evidenced the absence of radioactive elements in the collected soil samples of bauxite mining areas. However, results cannot be generalized for all bauxite mining areas of Kuantan district.